Stress echocardiography in coronary artery disease: a practical guideline from the British Society of Echocardiography - Richard P Steeds; Richard Wheeler; Sanjeev Bhattacharyya; Joseph Reiken; Petros Nihoyannopoulos; Roxy Senior; Mark J Monaghan; Vishal Sharma (Echo Research and Practice, 2019)
Stress echocardiography is an established technique for assessing coronary artery disease. It has primarily been used for the diagnosis and assessment of patients presenting with chest pain in whom there is an intermediate probability of coronary artery disease. In addition, it is used for risk stratification and to guide revascularisation in patients with known ischaemic heart disease. Although cardiac computed tomography has recently been recommended in the United Kingdom as the first-line investigation in patients presenting for the first time with atypical or typical angina, stress echocardiography continues to have an important role in the assessment of patients with lesions of uncertain functional significance and patients with known ischaemic heart disease who represent with chest pain. In this guideline from the British Society of Echocardiography, the indications and recommended protocols are outlined for the assessment of ischaemic heart disease by stress echocardiography.